INFORMATION SOCIETY TECHNOLOGIES IN THE STUDY PROCESS: TEACHERS’ PERSPECTIVE - Kankeviciene, Lina; Gedviliene, Genute; Vaiciuniene, Vilhelmina (European Scientific Journal, ESJ, 2014)
Today’s students represent a new, Web generation who has grown up surrounded by digital technology, where the ubiquitous communication is a matter of course (Prensky, 2001). Activities prevailing in modern learning process are communication, knowledge management and mastering new technologies. Broader opportunities for the new generation to access education and communication are the main reasons for the growing use of the new Information Society Technologies (ISTs): social networks, blogs, wikis, communities’ bookmarks, messaging and others (Redecker et al., 2010). Thus, advancement of the knowledge age, where lifelong learning is a necessity, guidance in a new learning paradigm, the European dimension in education are the factors that determine the relevance of new ways of teaching and learning adapted to students’ specific ways of thinking and based on new IST. So, IST application in teaching/learning process implies not only new opportunities, but also challenges for the teacher: there is a need for the competence, enabling efficient application of IST in teaching/learning process while seeking educational aims. This article aims to identify teachers’ use of ISTs, their attitudes in respect to the IST use, encountered pitfalls and barriers.